2018
DOI: 10.1136/bmjopen-2018-023850
|View full text |Cite
|
Sign up to set email alerts
|

Triangulating abuse liability assessment for flavoured cigar products using physiological, behavioural economic and subjective assessments: a within-subjects clinical laboratory protocol

Abstract: IntroductionIn the USA, Food and Drug Administration regulations prohibit the sale of flavoured cigarettes, with menthol being the exception. However, the manufacture, advertisement and sale of flavoured cigar products are permitted. Such flavourings influence positive perceptions of tobacco products and are linked to increased use. Flavourings may mask the taste of tobacco and enhance smoke inhalation, influencing toxicant exposure and abuse liability among novice tobacco users. Using clinical laboratory meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Forty-nine percent ( n = 24) of articles provided participants with instructions to respond as though the cigarettes were their favorite ( n = 19) or preferred ( n = 5) brand, whereas 12% ( n = 6) of articles instructed participants to respond as though the cigarettes were their usual ( n = 5) or typical ( n = 1) brand. One article (Wall et al, 2018) specified the brand was the session cigarette experienced by the participants prior to completing the CPT and the remaining 37% ( n = 18) of articles reported no information about the quality of the cigarettes specified in the instructions. With respect to financial assumptions, 47% ( n = 23) of articles specified participants in the purchasing scenario should respond based on their present income and/or savings, while 4% ( n = 2) asked participants to consider their financial circumstances (Johnson, Johnson, Rass, & Pacek, 2017), or to respond based on their existing resources (Tucker, Laugesen, & Grace, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-nine percent ( n = 24) of articles provided participants with instructions to respond as though the cigarettes were their favorite ( n = 19) or preferred ( n = 5) brand, whereas 12% ( n = 6) of articles instructed participants to respond as though the cigarettes were their usual ( n = 5) or typical ( n = 1) brand. One article (Wall et al, 2018) specified the brand was the session cigarette experienced by the participants prior to completing the CPT and the remaining 37% ( n = 18) of articles reported no information about the quality of the cigarettes specified in the instructions. With respect to financial assumptions, 47% ( n = 23) of articles specified participants in the purchasing scenario should respond based on their present income and/or savings, while 4% ( n = 2) asked participants to consider their financial circumstances (Johnson, Johnson, Rass, & Pacek, 2017), or to respond based on their existing resources (Tucker, Laugesen, & Grace, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of articles reported framing prices as either per cigarette (59%; n = 29) or per cigarette with the yoked price per pack (33%; n = 16). Four percent ( n = 2) of articles used puffs as the units of consumption (per puff, Johnson et al, 2017; per 10 puffs, Wall et al, 2018), and the remaining 4% ( n = 2) of the articles did not report price framing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abuse liability refers to the likelihood of a drug to be used nonmedically and for its use to lead to dependence (Carter et al, 2009) and may be influenced by characteristics of the drug or drug delivery system, the individual user, and the social and policy environment. Several indices of abuse liability can be measured in the clinical laboratory, a setting that allows for efficient and controlled examination of subjective, physiological, and behavioral responses to the drug (Wall et al, 2018). However, few studies have examined abuse liability for cigars in the clinical laboratory (Blank, Cobb, Eissenberg, & Nasim, 2016; Blank, Nasim, Hart, & Eissenberg, 2011; Fabian, Canlas, Potts, & Pickworth, 2012), and none to our knowledge have examined the role of cigar flavors.…”
mentioning
confidence: 99%
“…Much of the recent published literature on flavored cigar use focuses on the impact of bans on flavored tobacco products, imposed at national [4] and local levels [5][6][7] over the past several years. Other studies have assessed potential abuse liability of flavored cigars [8,9], and/or examined various associations and impacts of flavored non-cigarette tobacco product use in general (i.e., aggregating the use of flavored e-cigarettes, smokeless tobacco, hookah, pipe, and cigar products into a singular construct) [10][11][12]. Some studies continue to cite sometimes decade or older trends [13][14][15] and relatively few studies have reported on recent prevalence and use of cigars in general or flavored cigar products specifically.…”
Section: Introductionmentioning
confidence: 99%